Finance and Growth for Microenterprises: Evidence from Rural China. (March 2015) - Beck, Thorsten; Lu, Liping; Yang, Rudai
Highlights: We examine the finance–growth nexus for microenterprises in China. Access to finance is positively associated with entrepreneurship. Informal finance is positively related with the growth of firms with employees. Informal finance is irrelevant for the growth of self-employed microenterprises. Formal finance is irrelevant for the sales growth of microenterprises. Summary: Using a survey dataset of Chinese rural households, we find that access to external finance is positively associated with the decision to become entrepreneur and the initial investment for microenterprises. Also, we find that use of informal finance, especially financing from friends and family, is positively associated with sales growth of microenterprises with employees, but not of self-employed. We do not find any significant relationship between the use of formal finance and firm growth. Our findings underline the importance of finance for entrepreneurship and microenterprise growth, and the role of informal finance in the absence of efficient formal financial institutions.